Cutaneous Biodistribution: A High-Resolution Methodology to Assess Bioequivalence in Topical Skin Delivery - Julie Quartier; Ninon Capony; Maria Lapteva; Yogeshvar N. Kalia (MDPI AG, 2019)
A draft guideline from the European Medicines Agency (EMA) highlights the need for methods to assess the quality/equivalence of topical drug formulations. The “cutaneous biodistribution method”, which provides insight into a drug’s spatial distribution in the epidermis/dermis, was used to compare cutaneous bioavailability of econazole nitrate (ECZ) from a reference medicinal product (RMP) and two approved bioequivalent generic creams under finite dose conditions. Statistically significant differences between the ECZ biodistributions from the RMP/Generics were determined and used with acceptance criteria based on those from the EMA to evaluate bioequivalence. In porcine skin, ECZ deposition in total skin, epidermis, upper and lower dermis from Generic 1 was within the acceptance interval, contrary to Generic 2, which was marginally below it. For human skin, Generic 1 deposition was marginally above the acceptance interval and not bioequivalent. The results were consistent with those using the EMA’s acceptance intervals using the ratio of the mean ECZ depositions of Generic 1 and the RMP. Differences identified using this data-rich technique may not translate to observable differences in clinical efficacy; however, generics with non-statistically different biodistributions to the RMP should have a comparable clinical effect. The cutaneous biodistribution method could benchmark the development of topical generic products.